2022
DOI: 10.1140/epje/s10189-022-00175-5
|View full text |Cite
|
Sign up to set email alerts
|

Active T1 transitions in cellular networks

Abstract: In amorphous solids as in tissues, neighbor exchanges can relax local stresses and allow the material to flow. In this paper, we use an anisotropic vertex model to study T1 rearrangements in polygonal cellular networks. We consider two different physical realizations of the active anisotropic stresses: (i) anisotropic bond tension and (ii) anisotropic cell stress. Interestingly, the two types of active stress lead to patterns of relative orientation of T1 transitions and cell elongation that are different. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…1b). This rigidity transition occurs at constant cell density and is driven by both active processes, such as fluctuations in cell-edge tension and cell motility [21][22][23][26][27][28][29][30] , as well as by geometric constraints 25,31 < l a t e x i t s h a 1 _ b a s e 6 4 = " e a u G s T r z F a 9 Z K P J 5 Y 5 c Q A p b K M r g = " > A A A B 7 H i c b V B N S 8 N A E J 3 U r 1 q / q h 6 9 L B a h p 5 K I q A c P B S 8 e K 5 i 2 0 I a y 2 W 7 a p Z t N 2 J 0 I J f Q 3 e P G g i F d / k D f / j d s 2 B 6 0 + G H i 8 N 8 P M v D C V w q D r f j m l t f W N z a x P k i 2 N n 5 M w q Q x I l 2 p Z C s l B / T u Q 0 N m Y a h 7 Y z p j g 2 q 9 5 c / M / r Z R h d B 7 l Q a Y Z c s e W i K J M E E z L / n A y F 5 g z l 1 B L K t L C 3 E j a m m j K 0 + V R s C N 7 q y 3 9 J + 7 z h X T a 8 + 4 t a s 1 7 E U Y Y T O I U 6 e H A F T b i D F v j A Q M A T v M C r o 5 x n 5 8 1 5 X 7 a W n G L m G H 7 B + f g G W e + N p g = = < / l a t e x i t > a = 0 < l a t e x i t s h a 1 _ b a s e 6 4 = " r f a Y 0 q i O V M N J j H j c A V + U m 3 M 0 w 5 w = " > A A A B 7 n i c b V D L S g N B E O y N r x h f U Y 9 e B o O Q U 9 g V U U 8 S 8 O I x g n l A s o T Z y W w y Z H Z 2 m O k V Q s h H e P G g i F e / x 5 t / 4 y T Z g 0 Y L G o q q b r q 7 I i 2 F R d / / 8 g p r 6 x u b W 8 X t 0 s 7 u 3 v 5 B + f C o Z d P M M N 5 k q U x N J 6 K W S 6 F 4 E w…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1b). This rigidity transition occurs at constant cell density and is driven by both active processes, such as fluctuations in cell-edge tension and cell motility [21][22][23][26][27][28][29][30] , as well as by geometric constraints 25,31 < l a t e x i t s h a 1 _ b a s e 6 4 = " e a u G s T r z F a 9 Z K P J 5 Y 5 c Q A p b K M r g = " > A A A B 7 H i c b V B N S 8 N A E J 3 U r 1 q / q h 6 9 L B a h p 5 K I q A c P B S 8 e K 5 i 2 0 I a y 2 W 7 a p Z t N 2 J 0 I J f Q 3 e P G g i F d / k D f / j d s 2 B 6 0 + G H i 8 N 8 P M v D C V w q D r f j m l t f W N z a x P k i 2 N n 5 M w q Q x I l 2 p Z C s l B / T u Q 0 N m Y a h 7 Y z p j g 2 q 9 5 c / M / r Z R h d B 7 l Q a Y Z c s e W i K J M E E z L / n A y F 5 g z l 1 B L K t L C 3 E j a m m j K 0 + V R s C N 7 q y 3 9 J + 7 z h X T a 8 + 4 t a s 1 7 E U Y Y T O I U 6 e H A F T b i D F v j A Q M A T v M C r o 5 x n 5 8 1 5 X 7 a W n G L m G H 7 B + f g G W e + N p g = = < / l a t e x i t > a = 0 < l a t e x i t s h a 1 _ b a s e 6 4 = " r f a Y 0 q i O V M N J j H j c A V + U m 3 M 0 w 5 w = " > A A A B 7 n i c b V D L S g N B E O y N r x h f U Y 9 e B o O Q U 9 g V U U 8 S 8 O I x g n l A s o T Z y W w y Z H Z 2 m O k V Q s h H e P G g i F e / x 5 t / 4 y T Z g 0 Y L G o q q b r q 7 I i 2 F R d / / 8 g p r 6 x u b W 8 X t 0 s 7 u 3 v 5 B + f C o Z d P M M N 5 k q U x N J 6 K W S 6 F 4 E w…”
mentioning
confidence: 99%
“…1b). This rigidity transition occurs at constant cell density and is driven by both active processes, such as fluctuations in cell-edge tension and cell motility, [21][22][23][26][27][28][29][30] as well as by geometric constraints. 25,31 Recent work by us and others has shown that even in the absence of fluctuations and topological rearrangements, vertex models exhibit a rigidity transition associated with geometrical frustration.…”
mentioning
confidence: 99%
“…Tissue remodeling and fluidization of biological tissue is enabled by exchange of neighboring cells by so-called T1 transitions. 28 A T1 transition is a topological rearrangement event, where one cell edge shrinks to a point and then expands in a perpendicular direction, resulting in the swap of neighboring cells. We observed a similar remodeling upon mechanically loading our structure (Movie M1, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8,21 As addressed below, energy barriers that typify the jammed system-which by definition is solid-like, elastic, and static--are not to be confused with frictional energy dissipation, and associated metabolic demands as would be required to propel a migrating unjammed system. 22,23…”
Section: Jamming In Confluent Tissuesmentioning
confidence: 99%